Synthesis and Chemistry of Organic Geminal Di- and Triazides - Andreas P. Häring; Stefan F. Kirsch (Molecules, 2015)
This review recapitulates all available literature dealing with the synthesis and reactivity of geminal organic di- and triazides. These compound classes are, to a large extent, unexplored despite their promising chemical properties and their simple preparation. In addition, the chemistry of carbonyl diazide (2) and tetraazidomethane (105) is described in separate sections.